The solar red-shift - Higgs, L (1961)
Shortly after Rowland's fundamental study of the wavelengths of Fraunhofer lines, Jewell in 1896 observed that the solar wavelengths were shifted to the red side of the corresponding wavelengths observed in the laboratory. This shift became known as the red shift of solar lines, and at first led to various erroneous concepts of conditions in the solar atmosphere. Moreover, in 1907, Halm discovered that the solar wavelengths were not themselves constant, but depended upon the radial distance of the point of observation from the centre of the solar disk. This variation of wavelength with the point of observation has now become known as limb effect. If θ is the angle between the line of sight to the point of observation on the solar surface and the true solar radius et that point, Λ (θ) denotes the difference between the wavelength at that position and that observed at the centre of the disk. In general, Λ (θ) was found to be positive, increasing toward the limb. Part of the general red shift of the Fraunhofer lines was explained when Einstein published his General Theory of Relativity, in which he predicted the Fraunhofer lines to be shifted to the red by an amount given by Δυ⁄υ = 2.12 × 10-6. In fact, this gravity shift is a consequence of the underlying Principle of Equivalence which ha a been recently demonstrated in the laboratory. On the other hand, no explanation of limb effect was immediately obvious. The most promising hypothesis was that of St. John, in which limb effect was attributed to the Doppler shifts arising from radial convective motions in the solar atmosphere. At the centre of the disk, these would be predominantly violet shifts while at the limb, the streaming would have no effect. Although satisfying some of the observational data, this interpretation was not wholly satisfactory. In particular, an interferometric determination of Λ (θ) by M. G. Adam in 1948 showed that, assuming known photospheric conditions, unreasonably large convective velocities were required for such an interpretation. Recently, Schröter has elaborated this theory of solar red shifts in which the gravity shift and Doppler shifts arising from unresolved granulation elements combine to give a red shift with limb effect. Again certain characteristics of the observed red shifts are accounted for, but consistent agreement with various observational data is lacking. The most serious difficulty in this respect was that the observations of M. G. Adam in 1969 indicated that at the extreme limb, the observed red shift exceeded the gravity shift. No theory based on radial convection currents can account for such a super-gravity shift. In order to submit the radial current theory to a detailed examination and to confirm the existence of a super-gravity shift, the wavelengths and profiles of three solar lines were studied. this investigation forms the subject matter of the thesis. The same three medium strength iron lines at 6300 A as used by M. G. Adam in her 1959 investigation were chosen, since they are conveniently situated for comparison with terrestrial lines of the α band of atmospheric oxygen. Using the latter as fixed wavelength references, the variation of the solar wavelengths across the disk was determined from micrometer measurements of grating spectra. After correction for the motions of the Earth and Sun and for the effects of scattered light, a mean Λ (θ) was determined for the three lines. It was found that Λ (θ) increased rapidly for radial distances from the centre of the disk greater than 85 per cent of the disk radius. Expressing the wavelength shifts as equivalent Doppler velocities, it was found that the value of Λ (θ) at the extreme limb was about 0.7 km/sec, in good agreement with the value found by M. G. Adam. In order to convert these observations to absolute red shifts (referred to terrestrial laboratory measurements), the wavelengths of the iron lines at the centre of the disk as well as in the laboratory were required. The interferometric method of circular channels was adopted for this purpose, and absolute wavelengths (referred to the cadmium line at λ 6438.4696) of the three iron lines and the oxygen reference lines in the spectrum obtained at the centre of the disk were determined. In order to confirm that the effects of local velocity fields in the photosphere had been eliminated from these observations, similar determinations of wavelengths were made using integrated light from the whole solar disk. In addition to the solar observations, the terrestrial wavelengths of the three Iron lines have been found using a vacuum iron arc. Combining these measurements with the limb effect observations gave a mean red shift et the centre of the disk of 0.39 km/sec increasing to about 1 km/sec at the limb. Since the gravity shift is 0.64 km/sec, the existence of a super-gravity shift at the limb is confirmed. Since the interpretation of micrometer measurements of limb effect depends critically on the centre-limb variation of the line profile concerned, in particular, of any asymmetry in the profile, the profiles of the three lines were determined for various disk positions, averaging many observations. It was found that at the centre of the disk the iron lines were slightly asymmetric with stronger violet than red flanks, somewhat as predicted by Schröter. At the limb, however, a large fluctuating red asymmetry was discovered. This is established to be of solar origin and appears to be connected in some manner with nearby chromospheric disturbances. This red asymmetry, occurring predominantly at residual line intensities ~ 0.8, on occasion corresponded to a shift of the line centre of 25 mA and was of sufficient mean magnitude to account for the super-gravity shift (if the micrometer measurements refer to such a residual intensity). An analysis of these observations of wavelength shifts and line asymmetry at the centre of the disk showed that Doppler shifts due to granulation, such as appear in Schröter's theory, are too small to account for the observations and, consequently, that the origin of the centre red shifts (actually the deviations from the gravity shift) must lie elsewhere. Moreover, the newly discovered red asymmetry, or alternatively the super-gravity shift, at the limb cannot have its origin in streaming motion. Following suggestions by H. H. Plaskett the possibility of this asymmetry being due to the superposition of a chromospheric line on the photospheric line was investigated. Such a superposition can arise from scattering or by chromospheric contributions to the profile in the line of sight. It was found that such a hypothesis could account for the observations if it is assumed that the chromospheric lines are shifted slightly to the violet. An additional section of the thesis deals with computational problems arising in the reduction of the wavelength and profile observations. Methods were developed for the utilization of the Oxford "Mercury" electronic computer for calculations such as the computation of corrections to observed wavelengths due to motions of the Sun and Earth, the reduction of circular channel interferometric plates, the determination of characteristic response curves of photographic plates, and the computation of true line profiles. In particular, a study of numerical methods of solving the integral equation arising in the instrumental broadening of spectral lines was made, and programmes for the solution of this equation were written. From this detailed study of the three medium strength iron lines, it is concluded that the origin of the solar red shift must be more complex than previously assumed. In addition to the gravity shift, small granulation effects, and possible chromospheric effects at the limb, some other, unknown, cause of wavelength shifts remains. Thus a new theoretical treatment of possible mechanisms for the creation of line shifts in the photosphere is required before a comprehensive red shift theory can be attained.